UIN : ONTOLOGIS, EPISTEMOLOGIS DAN AKSIOLOGIS - Lazuardi, Lazuardi (IAIN Padangsidimpuan, 2013)
Transforming IAIN to UIN is a scientific project. So the crucial thing to do is to reform scientific paradigm to the new scientific paradigms based on integrality. AtÂ last, the graduations will have academic competence, innovative and can guide people in the spirit of science and religion.